2015
DOI: 10.5799/ahinjs.01.2015.02.0499
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hand dysfunction in patients receiving hemodialysis through arteriovenous fistula

Abstract: ÖZETAmaç: Hemodiyaliz tedavisi alan hastalar genellikle arteriovenöz fistülün olduğu üst ekstremitelerini kullanmaktan kaçınırlar ve bu durum el fonksiyonlarının bozulmasıyla suçlanmaktadır. Bu hastalarda ele ait komplikasyonlara ilişkin bilgiler yetersizdir. Bu pilot çalışmanın amacı, hemodiyaliz tedavisi alan hastalarda her iki elin kavrama ve çimdikleyici kuvvetlerini ve böylece fonksiyonel durumunu incelemektir.Yöntemler: Hemodiyaliz tedavisi alan 15 kronik böbrek yetmezliği hastası (30-83 yaş) ve aynı yaş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Any injuries of the hand causes losses in functionality [9]. It was demonstrated that limitations in hand negatively affect participation and independency in small joint osteoarthritis in hands and kidney disease patients undergoing haemodialysis [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Any injuries of the hand causes losses in functionality [9]. It was demonstrated that limitations in hand negatively affect participation and independency in small joint osteoarthritis in hands and kidney disease patients undergoing haemodialysis [10,11].…”
Section: Introductionmentioning
confidence: 99%